Get Me Here: Using Verification Tools to Answer Developer Questions - Barnett, Mike; DeLIne, Robert; Lal, Akash; Qadeer, Shaz (2014)
While working developers often struggle to answer reachability questions (e.g. How can execution reach this line of code? How can execution get into this state?), the research community has created analysis and verification technologies whose purpose is systematic exploration of program execution. In this paper, we show the feasibility of using verification tools to create a query engine that automatically answers certain kinds of reachability questions. For a simple query, a developer invokes the “Get Me Here" command on a line of code. Our tool uses an SMT-based static analysis to search for an execution that reaches that line of code. If the line is reachable, the tool visualizes the trace using a Code Bubbles representation to show the methods invoked, the lines executed within the methods and the values of variables. The GetMeHere tool also supports more complex queries where the user specifies a start point, intermediate points, and an end point, each of which can specify a predicate over the program's state at that point. We evaluate the tool on a set of three benchmark programs. We compare the performance of the tool with professional developers answering the same reachability questions. We conclude that the tool has sufficient accuracy, robustness and performance for future testing with professional users.